2023
DOI: 10.1002/csc2.20926
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pollination traits important for hybrid wheat development in Great Plains germplasm

Abstract: Hybrid wheat (Triticum aestivum L.) offers potential yield advantages over conventional inbred cultivars. For hybrid wheat to be a commercial success, the cost to produce the hybrid seed needs to be minimized. Although wheat is naturally self‐pollinated, hybrid wheat seed production can be improved by increasing the amount and availability of pollen for cross‐pollination. This research examined 19 pollination traits using the Hard Winter Wheat Association Mapping Panel for 3 years. Anther extrusion, pollen 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…(2002) suggested that well‐spaced spikes carrying large lodicules, a soft lemma, and palea would facilitate the wide opening of each floret. Environmental and genotypic variability here reported for male floral traits under field conditions were partially documented for AE (Boeven et al., 2016; Garst et al., 2023; Langer et al., 2014; Muqaddasi et al., 2016; Muqaddasi, Brassac, et al., 2017; Muqaddasi, Pillen, et al., 2017; Sade et al., 2022), AL (Komaki & Tsunewaki, 1981; Nguyen et al., 2015; Song et al., 2018), and AFL (Beri & Anand, 1971; Denisow et al., 2022). Our results showed that the degree of dwarfism produced by the different combinations of Rht genes resulted in significant reductions in parameters of strategic importance for the development of elite pollinators needed for hybrid wheat breeding programs.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…(2002) suggested that well‐spaced spikes carrying large lodicules, a soft lemma, and palea would facilitate the wide opening of each floret. Environmental and genotypic variability here reported for male floral traits under field conditions were partially documented for AE (Boeven et al., 2016; Garst et al., 2023; Langer et al., 2014; Muqaddasi et al., 2016; Muqaddasi, Brassac, et al., 2017; Muqaddasi, Pillen, et al., 2017; Sade et al., 2022), AL (Komaki & Tsunewaki, 1981; Nguyen et al., 2015; Song et al., 2018), and AFL (Beri & Anand, 1971; Denisow et al., 2022). Our results showed that the degree of dwarfism produced by the different combinations of Rht genes resulted in significant reductions in parameters of strategic importance for the development of elite pollinators needed for hybrid wheat breeding programs.…”
Section: Discussionmentioning
confidence: 60%
“…The degree of this response was genotype and environment‐dependent. The effect of the different dwarfing alleles reducing AE was clearer under high‐yield potential environments like those explored under German conditions (Figures S1b and S2b) due to longer photoperiod and optimal temperatures that increase pollination duration compared to Argentinian conditions (Garst et al., 2023; Jones et al., 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation